Preface - du Plessis, Theodorus; Cuvelier, Pol (Acta Academica: Critical views on society, culture and politics, 2006)
The contributions to this Acta Academica Supplementum result from research related to the Multilingual Information Development Programme (MIDP) of the Unit for Language Management that is funded in its entirety by the Province of Antwerp, Flanders, Belgium. The views expressed in this Supplementum, however, reflect the position of the individual authors.